Correlation between structure characteristics and pair radial distribution function in Silica glass under compression - Mai, Thi Lan (H. : ĐHQGHN, 2019)
We have studied structure of silica glass at different pressures and temperature of 300K by using Molecular Dynamics simulation (MD) method. The model consists of 6000 atoms (2000 Si, 4000 O atoms) with the periodic boundary condition. We applied the Morse-Stretch potentials which describe the pairwise interactions between ions for SiO2 system. There is structural phase transformation from tetrahedra (SiO4) to octahedra (SiO6) network structure. There is splitting in the Si-Si pair radial distribution function (PRDF) at high pressure (100 GPa). The original of this splitting relates to the edge- and face-sharing bonds. The new second peak of the O-O PRDF at the high pressure originates from oxygen atoms of the edge-sharing bonds. Thus, there is rearrangement of O atoms. O atoms have tendency to more order arrangement that leads to form some oxygen hcp and fcc structure in the model at high pressure.